Metabolism of aromatic acids in the antibiotic-producing basidiomycete Oudemansiella mucida - Zouchová, Z; Wurst, M; Nerud, F; Musílek, V (Folia microbiologica, 1982)
Aromatic acids were determined in the mycelium and fermentation medium of Oudemansiella mucida. Coumaric acids (both m- and p-), p-hydroxybenzoic acid (salicylic acid) and benzoic acid were found to predominate in the mycelium. Phenylacetic acid represents the main component in the medium. Phenylalanine ammonia-lyase catalyzing conversion of phenylalanine to cinnamic acid which is further metabolized to benzoic acid was detected in the mycelium. The results are discussed with respect to the synthesis of the antibiotic mucidin.
Keywords: nenasycené mastné kyseliny; Phenylalanine; Strobilurins; alkeny; methakryláty; strobiluriny; Methacrylates; Basidiomycota; hydroxybenzoáty; fenylacetáty; fenylalanin; Cinnamates; Phenylacetates; Alkenes; Benzoates; Hydroxybenzoates; cinnamáty; Fatty Acids, Unsaturated; benzoáty